2014
DOI: 10.1161/jaha.114.001127
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Physical Activity, and Their Interaction in Incident Atrial Fibrillation in Postmenopausal Women

Abstract: BackgroundAtrial fibrillation (AF) is the most common cardiac arrhythmia and is associated with increased risk of stroke and death. Obesity is an independent risk factor for AF, but modifiers of this risk are not well known. We studied the roles of obesity, physical activity, and their interaction in conferring risk of incident AF.Methods and ResultsThe Women's Health Initiative (WHI) Observational Study was a prospective observational study of 93 676 postmenopausal women followed for an average of 11.5 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
84
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 44 publications
2
84
0
3
Order By: Relevance
“…A similar interaction was observed in an analysis from the WHI, in which obese women had a lower risk of AF from increased levels of physical activity. 21 Our study has important implications for obese individuals and suggests that obese individuals may potentially benefit by strategies that can improve CRF, provided that CRF is causally associated with AF. There are many plausible mechanisms for this interaction.…”
Section: Discussionmentioning
confidence: 83%
“…A similar interaction was observed in an analysis from the WHI, in which obese women had a lower risk of AF from increased levels of physical activity. 21 Our study has important implications for obese individuals and suggests that obese individuals may potentially benefit by strategies that can improve CRF, provided that CRF is causally associated with AF. There are many plausible mechanisms for this interaction.…”
Section: Discussionmentioning
confidence: 83%
“…One recent study demonstrated that greater physical activity was associated with lower rates of AF in postmenopausal women [36], but risk factors associated with AF in the general population are still not clear. The vast majority of our subjects were agricultural workers with high levels of physical activity, which may have contributed to the low prevalence of AF in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this connection, the American Diabetes Association (ADA) recommends aerobic exercise of medium intensity such as 150 minutes of walking per week, or 75 minutes of high intensity aerobic exercise per week for patients with type 2 diabetes [22]. Previous studies showed that only 28% of postmenopausal women perform regular physical activity [23,24]. Despite the beneficial effects of physical activity, there are many complications to achieving the predicted improvement in health.…”
mentioning
confidence: 99%